2002
DOI: 10.2307/2697116
|View full text |Cite
|
Sign up to set email alerts
|

Cold War in the Kitchen: Gender and the De-Stalinization of Consumer Taste in the Soviet Union under Khrushchev

Abstract: Consumption, a key issue in the study of post-Soviet culture, was already a central concern during the Cold War. In the late 1950s and early 1960s, the Khrushchev regime staked its legitimacy at home, and its credibility abroad, on its ability to provide its population with consumer goods and a decent standard of living. Despite promising "abundance for all" as the precondition for the imminent transition to communism, the regime could not afford to leave abundance undefined. In this article, Susan E. Reid exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(47 citation statements)
references
References 21 publications
1
45
0
1
Order By: Relevance
“…Additionally, the production and consumption of various electronic appliances, such as refrigerators, washing machines and televisions, increased significantly in the post-war decades (Hanson, 2014). Although the Soviet regime argued for abandoning bourgeois consumerist practices, consumption became a 'crucial concern in the Soviet response to the Cold War' as Khrushchev's regime recognised the need to increase the quantity, quality and range of consumer goods in order to improve living standards, particularly those of nuclear families (Hanson, 2014;Lapidus, 1978;Reid, 2002Reid, , 2009). The particularity of Soviet consumer culture was that while shortages were visible in all areas of life, from food and clothing to electronics and housing, they were still possible to acquire.…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the production and consumption of various electronic appliances, such as refrigerators, washing machines and televisions, increased significantly in the post-war decades (Hanson, 2014). Although the Soviet regime argued for abandoning bourgeois consumerist practices, consumption became a 'crucial concern in the Soviet response to the Cold War' as Khrushchev's regime recognised the need to increase the quantity, quality and range of consumer goods in order to improve living standards, particularly those of nuclear families (Hanson, 2014;Lapidus, 1978;Reid, 2002Reid, , 2009). The particularity of Soviet consumer culture was that while shortages were visible in all areas of life, from food and clothing to electronics and housing, they were still possible to acquire.…”
Section: Contextmentioning
confidence: 99%
“…However, recent studies of everyday lives under capitalism and communism offer a different narrative. They have shown that individual realities on both sides of the Iron Curtain were, in fact, not that different and often surrounded by similar struggles to meet certain living standards and private life aspirations (Carter, 1997;Gerchuk, 2000;Reid, 2002Reid, , 2009Reid & Crowley, 2000;Zakharova, 2013). More importantly, the convergence in fertility rates in Western and Eastern Europe around the two-child family ideal also suggests that some similar processes were happening on the micro-level.…”
Section: Introductionmentioning
confidence: 99%
“…While "frumpy women" did little to help raise support for socialist ideals, the presence of Western fashion was representative of consumerism and Western indulgence. However, this ideological paradox was addressed through a distinct and plain Soviet fashion (Reid, 2002). This symbolically simple style represented a way to distinguish the Soviet Union from the West as well as create an image of the ideal woman.…”
Section: Fashion In the "Punk Prayer"mentioning
confidence: 99%
“…Household was to be a space of modernity -both in the sphere of production, when it helped 'handle' the family and satisfy its members' needs such as food, clothing, hygiene, and in the sphere of consumption -when household was to facilitate respite and repose while encouraging the comfort of privateness. Since the 'kitchen debate' (held in 1959 in Moscow on the occasion of the American National Exhibition and described many a time in literature), 17 a modernised individual household, equipped with dedicated appliances, became an epitome of a new type of rivalry against the West: it was meant to prove that the socialist state was ready to ensure adequate levels or standards of consumption to its citizens. The inward discourse, targeted at the country's citizens, praised the household as a promise of progress and incessant improvement of the living conditions.…”
mentioning
confidence: 99%